Design and Comparison of Grid Connected Permanent Magnet Synchronous Generator Non-salient Pole and Salient Pole Rotor Wind Turbine - S.M. Mehedi Hasan (AIUB Journal of Science and Engineering (AJSE), 2021)
Variable speed wind turbines are widely used wind energy conversion system (WECS). Among them doubly fed induction generator (DFIG) and permanent magnet synchronous generator (PMSG) are mostly used. PMSG based wind turbines are getting more popular in recent times because of their several advantages over other types. Direct drive capability and low speed operation are some of its significant advantages over other type. In the dq0 reference frame, this analysis discusses the implementation and simulation of a Simulink-based operated permanent magnet synchronous generator (PMSG) wind turbine. The current control subsystem makes use of PID controllers to regulate the wind turbine's velocity, direct and quadrature stator currents, and blade pitch tilt. The pitch angle controller monitors both the generator's speed and active strength, restricting both in the event of high-speed wind conditions. PMSGs exhibit constant excitation that is uncontrollable. As a result, a properly designed damper winding is needed to ensure stable operation in the absence of a frequency controller. This article analyzes and compares the performance of three-phase non-salient pole permanent magnet ac machines and salient pole machine fitted with damper windings in rigid network operation. The recommendations for network-connected generators are determined by evaluating the results of a circuit-based mathematical models of the PM-machine. Variable speed wind turbines are widely used wind energy conversion system (WECS). Among them doubly fed induction generator (DFIG) and permanent magnet synchronous generator (PMSG) are mostly used. PMSG based wind turbines are getting more popular in recent times because of their several advantages over other types. Direct drive capability and low speed operation are some of its significant advantages over other type. In the dq0 reference frame, this analysis discusses the implementation and simulation of a Simulink-based operated permanent magnet synchronous generator (PMSG) wind turbine. The current control subsystem makes use of PID controllers to regulate the wind turbine's velocity, direct and quadrature stator currents, and blade pitch tilt. The pitch angle controller monitors both the generator's speed and active strength, restricting both in the event of high-speed wind conditions. PMSGs exhibit constant excitation that is uncontrollable. As a result, a properly designed damper winding is needed to ensure stable operation in the absence of a frequency controller. This article analyzes and compares the performance of three-phase non-salient pole permanent magnet ac machines and salient pole machine fitted with damper windings in rigid network operation. The recommendations for network-connected generators are determined by evaluating the results of a circuit-based mathematical models of the PM-machine.